Quartz Enhanced Photoacoustic Spectroscopy for Detection of Improvised Explosive Devices and Precursors. (1st February 2016) - Viola, Roberto; Liberatore, Nicola; Luciani, Domenico; Mengali, Sandro
Abstract : A compact portable and standalone point sensor has been developed for the detection and identification of precursors of improvised explosive devices (IEDs) and to be part of a network of sensors for the discovery of hidden bomb factories in homeland security applications. The sensor is based on quartz enhanced photoacoustic spectroscopy (QEPAS), and it implements a broadly tunable external cavity quantum cascade laser source (EC-QCL). It makes use of an optical cell purposely designed with a miniaturized internal volume, to achieve fast response and high sensitivity, and that can also be heated to improve sensitivity towards less volatile compounds. The sensor has been assembled and successfully tested in the lab with several compounds, including IED's precursors such as acetone, nitromethane, nitric acid, and hydrogen peroxide. The identification capability and limits of detection near the ppm level have been estimated for all these compounds.